Heat Transfer Performance of Capillary Heat Exchangers in Circular Tunnel Lining during Intermittent Operation - Jiao Jiachen; Ji Yongming; Zhang Fengjun; Ji Chengfan; Yin Zhenfeng; Hu Songtao (Zhileng xuebao)
Tunnel ground-source heat pumps are effective in solving the thermal pollution problem in subway tunnels. A capillary-tube heat exchanger (CHE) is used as the front-end heat exchanger of the tunnel ground-source heat pump system because of its corrosion resistance, easy bending, good heat transfer performance, and compactness. In this study, a CHE fluid-thermal coupling heat transfer model is established based on a demonstration project, and a CHE simulation system is built on the TRNSYS platform to analyze the heat transfer performance of the CHE in tunnel linings under continuous and intermittent operation. When the run-time ratio increases from 1/3 to 1, the average daily heat flux of CHE in the cooling and heating seasons decreases from 100.59 W/m2 and 87.42 W/m2 to 78.14 W/m2 and 68.62 W/m2 after 7 days, respectively, whereas the inner surface temperature of the surrounding rock increases and decreases in the cooling and heating seasons, respectively. The results show that intermittent operation can significantly improve the heat transfer performance of the heat exchanger and help alleviate the problem of cold and heat accumulation in the rock surrounding the tunnel.